(untitled) (Latakia University Journal -Biological Sciences Series, 2019)
تم دراسة تأثير طريقة استخلاص الكاراجينان من الطحلب هيبنيا ميسيفورميسHypnea musciformis (Wulfen) Lamouroux بطريقتين مع زمن استخلاص متغير من 1 6-ساعات وتأثير ذلك في مردوده وبعض خواصه الفيزيائية, تبين أنه كلما زاد زمن الاستخلاص ارتفع المردود, ولكن انخفضت جودة خواصه الفيزيائية. إن أعلى مردود للكاراجينان بحسب الأولى العادية %47 وقوة الهلام 2cm/g230 واللزوجة Pc30.6 أما درجة حرارة الذوبان C °71 والتجمد C° 48, وبالطريقة الثانية بإضافة قلوي المردود %39 وقوة الهلام 2cm/g 244 واللزوجة Pc36.4 ودرجة حرارة الذوبان C° 74 والتجمد C° 50. Effect of carrageenan extraction method from marine alga Hypnea musciformis (Wulfen) Lamouroux has been studied, by two methods with time extraction 1-6 hours on the carrageenan yield and some of its physical properties, shows that the yield is highest with increased time extraction, but the physical properties of carrageenan decreased. The highest yield for native carrageenan is 47% and the gel strength 230 g/cm2, The viscosity is 30.6 cP while melting temperature 71°C and gelling 48°C, The yield for alkali carrageenan is 39%, the gel strength 244 g/cm2, The viscosity is 36.4cP while melting temperature 74°C and gelling 50°C.